Consultant Perceptions of Electronic Online Workplace‐Based Assessment Training for Surgical Trainees in the United Kingdom. (2nd September 2014) - Fu, Bertram; Hampton, Tom; Haarer, Francesca; Das, Prodip
Abstract : Objectives: (1) Describe the online electronic Work‐Based Assessments (WBAs) tools (run by Intercollegiate Surgical Curriculum Programme [ISCP]) used by consultant trainers in surgical training in the United Kingdom. (2) Describe the current perceptions and prior training (TrACE‐Training and Assessment in the Clinical Environment) received by consultant trainers of such training tool. Methods: An anonymous electronic survey was circulated to all surgical educational supervisors within a large southeast England university teaching hospital in the period of August‐December 2013. Results: Twenty‐one consultants were identified. Seventeen responded (81%), all using WBAs in ISCP. Only 1 supervisor had heard of TrACE, and 17% had received no formal training in verifying themselves as competent in their assessor role. Thirty‐five percent felt they would like to receive formal ISCP training, with the remainder happy to self‐certify their competency. Conclusions: The GMC specifies that trainers must be competent in the use of WBAs and the ISCP cites a need for systematic accreditation of supervisors. The RCSEng runs TrACE course, which explains roles/responsibilities of a trainer/supervisor with regard to the use of WBAs. Supplementary to the "Training the Trainers" course, it offers a structured forum to discuss recent changes in postgraduate training. We conducted this study to assess awareness/uptake/thought regarding changes in surgical supervision to identify whether the guidelines are being implemented. We recommend increased publicity for this and similar courses providing consultants for this training. The alternative is a more formal adoption of current status quo whereby consultants appointed as supervisors and assessors self‐certify their competency in supervising juniors.